Instrument Flourishing Adolescence Scale: Validating a Comprehensive Well-being Measure Using the Rasch Model - Diki Herdiansyah; Rohmatus Naini (Universitas Mercu Buana Yogyakarta, 2025)
This study aimed to develop and validate the instrument flourishing adolescence scale (I-FAS) as a comprehensive tool to measure adolescent flourishing, particularly for use in guidance and counseling contexts. The instrument was developed based on five key dimensions: psychological, social, subjective, emotional, and spiritual well-being. The development process included theoretical framework analysis, item construction, expert validation , and a pilot test to assess clarity and readability. Revisions were made before large-scale testing. A quantitative approach was used to evaluate the psychometric properties of the instrument through the Rasch Model. Data were collected via an online survey from 400 junior and senior high school students in Yogyakarta. The results showed that the I-FAS met the unidimensionality criteria, with a raw variance explained of 31.4%, exceeding the 20% threshold. The instrument also demonstrated strong internal consistency (Cronbach's Alpha = 0.92), high person reliability (0.90), and item reliability (0.99). The item difficulty range was acceptable, with the most difficult item having a measure of +1.89 and the easiest –1.76. Five items were identified as misfitting and considered for revision. These findings support that the I-FAS is a valid, reliable, and culturally relevant instrument for measuring adolescent flourishing. The inclusion of spiritual well-being provides added value in cultural contexts where spirituality plays a key role. The I-FAS can assist counselors and educators in identifying student needs and designing targeted interventions to support their well-being and development